Orthogonal Generalized Higher k-Derivation on Semi Prime Г-Rings - Abd-Ali, Hajer Hamed; Salih, Salah Mehdi (Iraqi Journal of Science, 2023)
The definition of orthogonal generalized higher k-derivation is examined in this paper and we introduced some of its related results.